The Dynamics of Communication in Ruqyah Sharia on Youtube: A Pragmatics Analysis of Interactions between Ustadz and the Patients - Suparno, Darsita; Saehudin, Akhmad; Nurhuda, Zam Zam; Lutfi, Mukhamamd; Maharani, Sabrina; Mahfudhoh, Vina Ulva (Muslim English Literature, 2023)
This study aims to identify linguistic expressions on utterances used in communication during ruqyah sharia happening. It is conducted using a pragmatic perspective and the descriptive qualitative method in analyzing data. Data from this research got from Youtube during the treatment of ruqyah sharia. This study used maxim theory to test the use of the cooperative principles among them during ruqyah sharia so we can get a system of the cooperative principle which is violated or obeyed by them. Based on findings and discussion, it can be seen the following. There are some conversations which violated by Ustadz and the patient conversation. There are about 2% violated the maxim of manner, 8% violated the maxim of relation, 5% violated the maxim of quality, and 3% violated the maxim of quantity. Some conversations are obeyed, namely 40 % obeyed the maxim of manner, 16 % obeyed the maxim of relation, 34% obeyed the maxim of quality, and 10 % obeyed the maxim of quantity. Based on these findings, it can be concluded that in ruqyah sharia, the theory of Grice (1975) about the cooperative principle can be tested in the use of the cooperative principle between ustadz and patients in the Indonesian context. Although the patient did not aware of his conversation, he can make good cooperative principles with Ustadz so the conversation can go smoothly and both speakers understand their conversation.